Waldmann's disease: a rare cause of protein losing enteropathy in an adult patient - Cláudio Martins (Revista Espanola de Enfermedades Digestivas)
Primary intestinal lymphangiectasia or Waldmann's disease is an uncommon cause of protein losing enteropathy with an unknown etiology and is usually diagnosed during childhood. It is characterized by dilation and leakage of intestinal lymph vessels leading to hypoalbuminemia, hypogammaglobulinemia and lymphopenia. Differential diagnosis should include erosive and non-erosive gastrointestinal disorders, conditions involving mesenteric lymphatic obstruction and cardiovascular disorders that increase central venous pressure. Since there are no accurate serological or radiological available tests, enteroscopy with histopathological examination based on intestinal biopsy specimens is currently the gold standard diagnostic modality of intestinal lymphangiectasia. We report a rare case of a primary intestinal lymphangiectasia in a 60-year-old Caucasian female who presented with asymptomatic hypoalbuminemia and hypogammaglobulinemia. After the diagnosis of a protein losing enteropathy, the patient underwent an enteroscopy and biopsies were taken, whose histological examination confirmed dilated intestinal lymphatics with broadened villi of the small bowel. Secondary causes of intestinal lymphangiectasia were excluded and the diagnosis of Waldmann's disease was recorded. The patient was put on a high-protein and low-fat diet with medium-chain triglyceride supplementation with improvement.